COVID-19 information spaces, boundaries, and information sharing: an interview study - Togzhan Seilkhanova; Theodore Dreyfus Ledford; Jodi Schneider (Information Research: An International Electronic Journal)
Introduction. The goal of this paper is to understand who shares information used by the general public about COVID-19 and how they decided what information to share.